Success of the Establishment Stage in Group Counseling - Oktari, Melandi; Lestari, Ayu; Rahmi, Alfi; Oktarini, Ira; Sabarrudin, Sabarrudin (Darul Yasin Al Sys, 2023)
Group counseling is a strategy in guidance and counseling that is assistance provided by utilizing group dynamics by discussing a personal problem of the group members. The formation stage is the initial stage which is very influential in further activities. At this stage, the formation of a group structure marks it. This research aims to discover the proper steps to take in the formation stage of group counseling. The research method is library research, which uses library data expansion methods, reading and recording, and processing research materials. The study results revealed that the group leader's Role in the formation stage dramatically determines the success of group counseling activities. It is hoped that the group leader is genuinely active and can ask, answer, feel, provide feedback, and control the group's game to create good dynamics.